ANALISIS PENGARUH PROFITABILITAS TERHADAP NILAI PERUSAHAN PADA SUB SEKTOR PROPERTI DAN REAL ESTATE DI BURSA EFEK INDONESIA - Nurwahidah Nurwahidah; Syaumuddinsyah; Nasruddin; Suryaningsih (Journal Ilmiah Rinjani : Media Informasi Ilmiah Universitas Gunung Rinjani, 2026)
This study aims to analyze the effect of profitability on firm value in property and real estate companies listed on the Indonesia Stock Exchange during the 2014–2018 period. Profitability is proxied by Return on Equity (ROE), while firm value is measured using Price to Book Value (PBV). This research employs a quantitative approach using secondary data obtained from the companies' financial statements. The sample consists of 10 companies with 50 observations selected through purposive sampling. Data were analyzed using descriptive statistics, classical assumption tests, and simple linear regression analysis. The results indicate that profitability has a positive and statistically significant effect on firm value, with a significance value of 0.002 (<0.05). These findings imply that higher profitability enhances firm value by increasing investors' confidence in the company's future prospects. Therefore, improving profitability is an important strategy for companies to maximize firm value and strengthen their competitiveness in the capital market. Keywords: Profitability, Return on Equity, Firm Value, Price to Book Value, Indonesia Stock Exchange.